Left heart Impella-device to bridge acute mitral regurgitation to MitraClip-procedure: a novel implementation of percutaneous mechanical circulatory support. (25th November 2020) - Vandenbriele, C; Balthazar, T; Wilson, J; Ledot, S; Smith, R; Caetano, A.F; Adriaenssens, T; Goetschalckx, K; Janssens, S; Dubois, C; Jacobs, S; Meyns, B; et al.
Abstract: Background: Acute mitral regurgitation (MR) is an emergency, often requiring urgent surgery. Severe acute MR presenting with hemodynamic collapse is usually caused by papillary muscle rupture or dysfunction after acute myocardial infarction (AMI) or chordal rupture, resulting in flail mitral leaflet(s). Preoperative stabilization is complex due to concomitant hemodynamic collapse and hypoxic respiratory failure. Finding the right balance between both preload and inotropic support is challenging. When patients are too sick for immediate surgical intervention, mechanical circulatory support can be considered because of its ability to both unload and reduce of cardiac work while increasing coronary perfusion and cardiac output. Nevertheless, even after initial stabilization, surgical risk remains high in critically ill acute severe MR patients and transcatheter treatments such as MitraClip are increasingly being explored. Methods: Between August 2017 and September 2019, patients presenting with acute severe mitral regurgitation and considered too ill for immediate surgical intervention (EURO-II score >11.2% plus pulmonary oedema necessitating mechanical ventilation and/or hemodynamic instability), were selected for an Impella-assisted LV unloading technique as bridge to MitraClip-procedure. Five patients were selected for the combined left Impella/MitraClip-procedure in two tertiary cardiac ICUs. Results: The mean age was 72 years. The cause of MR was ischemic in 20% and all patients presented in cardiogenic shock state, necessitating mechanical ventilation. The overall cardiac operative risk assessment (Euro-II) score predicted a 35% chance of in-hospital mortality. Cardiac output was severely impaired (mean LVOT VTI 8.2 cm). All patients were on inotropic support and supported by an Impella-CP pVAD (mean flow 2.5 Liter per minute; mean 6.3 days of support). In all cases, we managed to reduce the LVEDP below 15 mmHg using the combination of medical therapy (afterload reduction, inotropes), mechanical ventilation and pVAD-therapy. The MR was significantly reduced by a MitraClip-procedure in each Impella supported patient. The overall survival at discharge was 80%. One patient with late referral and multiple organ failure at presentation deceased due to refractory cardiogenic shock. Overall, severe MR was reduced to grade 1+ and all four patients survived 6 months after discharge with only one readmission for decompensated heart failure. Conclusions: A combined strategy of Impella and MitraClip appears to be a novel, feasible alternative for patients presenting with acute, severe MR unable to proceed to a corrective surgical procedure at presentation due to severe left ventricular forward flow failure. In these cases, the early initiation of pVAD-support may reduce the risk of development of irreversible end- organ damage and dysfunction. Exploration in a larger, randomised population is warranted to investigate this strategy further. Funding Acknowledgement: Type of funding source: None